Longitudinal relations of executive functions to academic achievement and wellbeing in adolescence - M. Jennifer Kitil; Adele Diamond; Martin Guhn; Kimberly A. Schonert-Reichl (Frontiers in Education)
IntroductionExecutive functions (EFs) are essential for cognitive, social, and emotional competence and have important implications for developmental outcomes across the lifespan. Limited research has explored how EFs relate to academic achievement and well-being specifically in adolescence over time. This study investigated relations of EFs to grade point average (GPA) and well-being (life satisfaction, depressive symptoms) from early to late adolescence.MethodsData were collected using multiple methods from 65 students in 4th and 5th grades and then again in 11th and 12th grades.ResultsResults revealed that EFs and depressive symptoms in early adolescence predicted GPA eight years later. EFs and life satisfaction were also correlated in late adolescence.DiscussionGiven the malleability of EFs, these findings suggest early interventions to enhance EFs may improve academic achievement in high school.